The Decline of Tengklung Gobleg Bali Martial Arts: A Socio-Cultural Analysis in the Era of Globalization - I Gde Agoes Caskara Surya Putra; Nurita, Wayan; Ida Bagus Gde Nova Winarta (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study investigates the declining interest in Tengklung Gobleg, a traditional martial art from Gobleg Village, Buleleng, Bali. Employing a qualitative approach, data were collected through interviews, field observations, documentation, and literature review. The analysis drew on perspectives from globalization, social identity theory, and related concepts. The findings indicate several contributing factors to the decline: limited socialization, lack of awareness among the younger generation, paternalistic cultural patterns, insufficient institutional support, and a growing preference for instant gratification among potential trainees. A key insight from this study is the shift in youth perception—Tengklung Gobleg is increasingly seen as outdated, while martial arts from outside Bali and Indonesia are viewed as more appealing and relevant. This reflects a broader cultural shift influenced by global exposure and changing social values.